APPLICATION IN ACCOUNTING CYCLE ANALYSIS OF SMALL BUSINESS AND MEDIUM ENTERPRISES IN YOGYAKARTA SPECIAL REGION - Srikandi, Cut; Setyawan, Dr. Aris Budi (Accounting, 2010)
The role of SMEs in the economy in Indonesia is central, a large number of industries and found in every economic sector, its potential in employment when compared with large-scale enterprises as well as its contribution to GDP and foreign exchange through export of value to make SMEs to form a very calculated effort . The success of SMEs to survive in a crisis does not necessarily make the SMEs are able to develop well. SMEs still face many problems in running its business. The problem often faced by SMEs include product marketing, technology, quality human resources to financial management. Financial management through the application of accounting rules and good and right sometimes ignored the perpetrators of SMEs. This study aims to determine the extent to which the perpetrators of SMEs applying financial management through accounting cycles that can be used as a tool to assess the performance and health of SMEs, and to know the type of business where the application of accounting rules better. This study used a survey method that takes a sample of the population using a questionnaire. The survey was conducted in five districts spread across the territory of Yogyakarta., With respondents of 100 SMEs by using descriptive and inferential analysis as a tool of analysis. The research concludes that most SMEs are still far in applying the rules and accounting through the accounting cycle, and the type of manufacturing business was the application of accounting rules better than the efforts of goods and services. Therefore, it is hoped relevant parties in this case the local government in cooperation with other parties to give attention to the perpetrators of SMEs that face difficulties in applying the accounting rules in accordance with the standards so that the perpetrators of SMEs to realize the importance of accounting cycle to the successful implementation of their business and be able to apply them in the business. Keywords : accounting cycle, small business, medium enterprises